DESENVOLVIMENTO DE UM TRANSPORTADOR PNEUMÁTICO DE GRÃOS - Hoffmann, Roger S.; Bortolaia, Luis A.; Basso, Samuel; Ritter, Douglas; Valdiero, Antonio C.; Motta, Frederico B. d. (Salão do Conhecimento, 2013)
Resumo